THE ASSOCIATION BETWEEN TIME MANAGEMENT, SALARY, AND WORKLOAD ON EMPLOYEE WORK-LIFE BALANCE IN THE HOTEL INDUSTRY - Shahinah Shah Jahan; Rosmawati Deraman; Noor Azura Ahmad Shauri, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
The hospitality sector's challenging work environment significantly affects employees' work-life balance. Key issues include flexible, around-the-clock shifts, leading to poor time management and increased stress, which decreases job satisfaction. Salary disparities and insufficient compensation also contribute, forcing employees to work longer hours or take additional jobs, further complicating work-life conflict. High work pressure and long hours in the hotel industry exacerbate stress and health problems, negatively impacting employees' ability to balance work and personal life. Addressing these challenges through targeted policies and programs is crucial to improving employee satisfaction, reducing turnover, and enhancing the overall performance of the hotel industry. This study uses a quantitative research design to explore how time management, salary, and workload affect work-life balance among hotel employees in Kuala Lumpur, Malaysia. A structured questionnaire will gather data from a sample of 291 employees working in five-star hotels, selected through stratified random sampling to ensure diverse representation. Online surveys will be distributed via email and social media, with reminders to boost participation. Ethical guidelines, including informed consent and confidentiality, will be followed. Data will be analyzed using regression analysis to assess the individual and combined effects of the variables on work-life balance, with results interpreted through statistical tests.